2014
DOI: 10.2214/ajr.13.11243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Peripheral Arterial Disease With Unenhanced Quiescent-Interval Single-Shot MR Angiography at 3 T

Abstract: QISS MRA maintains high diagnostic performance at 3 T despite the challenges inherent to image acquisition at higher field strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
2
28
1
2
Order By: Relevance
“…Studies at 1.5 T demonstrated high sensitivity (87.0-98.6 %) and specificity (94.6-96.0 %) of QISS-MRA for detection of significant stenosis, using mainly CE-MRA as SOR [12][13][14]. QISS-MRA at 3 T was also investigated for assessment of PAD, again using mainly CE-MRA as SOR [17][18][19][20]. These studies demonstrated the feasibility of QISS-MRA at 3 T but yielded mixed results regarding diagnostic performance with sensitivity and specificity of 87.5-100 % and 76.5-98.5 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies at 1.5 T demonstrated high sensitivity (87.0-98.6 %) and specificity (94.6-96.0 %) of QISS-MRA for detection of significant stenosis, using mainly CE-MRA as SOR [12][13][14]. QISS-MRA at 3 T was also investigated for assessment of PAD, again using mainly CE-MRA as SOR [17][18][19][20]. These studies demonstrated the feasibility of QISS-MRA at 3 T but yielded mixed results regarding diagnostic performance with sensitivity and specificity of 87.5-100 % and 76.5-98.5 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial vascular tree was divided into 32 segments for analysis of image quality and diagnostic performance: abdominal aorta (1), pelvic vessel segments including right and left common iliac artery (2, 3), right and left external iliac artery (4,5), and right and left common femoral artery (6,7), thigh vessel segments including right and left deep femoral artery (8,9), right and left proximal and distal superficial femoral artery (10-13), right and left proximal, middle, and distal popliteal artery (14)(15)(16)(17)(18)(19), and calf vessel segments including right and left proximal and distal anterior tibial artery (20)(21)(22)(23), right and left tibiofibular trunk (24,25), right and left proximal and distal posterior tibial artery (26)(27)(28)(29), and right and left proximal and distal fibular artery (30-33). Two blinded readers (M.W.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NC-MRA has emerged as a potential diagnostic technique for PAD [20][21][22][23][24][25], with QISS MRA specifically demonstrating good accuracy for hemodynamic stenosis in diabetic patients. Whilst DSA can be performed with carbon dioxide as a contrast agent to prevent nephrotoxicity, image quality is poorer [15,16] and DSA remains an invasive procedure with attendant risks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several non-contrast MRA (NC-MRA) techniques have been developed to image peripheral arteries [20][21][22][23][24][25][26]. These include fresh-blood imaging, quiescent-interval single-shot (QISS) imaging, and flow-sensitizing dephasing gradient-prepared steady-state free precession imaging [20,25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%